2005
DOI: 10.1029/2005gl023800
|View full text |Cite
|
Sign up to set email alerts
|

ICESat range and mounting bias estimation over precisely‐surveyed terrain

Abstract: Prior to the launch of the Geoscience Laser Altimeter System (GLAS) on the Ice, Cloud and land Elevation Satellite (ICESat) in January 2003, topographic surveys were made by NASA's Airborne Topographic Mapper (ATM) over regions of the western United States and the Antarctic Dry Valleys to support calibration and validation of the range and pointing errors of GLAS lasers. Surveyed areas included terrain with large slopes, allowing pointing‐bias estimation with as little as a few seconds of ICESat data. Range er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 5 publications
(8 reference statements)
0
44
1
Order By: Relevance
“…GLA01 and GLA06 are the products used in this analysis. When fully calibrated, the global ICESat elevations are estimated to have an absolute accuracy of 2 to 7 cm and a precision of 2 to 3 cm at 40 Hz, tested over a variety of surfaces such as dry lakes and the Antarctic Dry Valleys Martin et al 2005;Magruder et al 2007). …”
Section: Icesat Datamentioning
confidence: 99%
“…GLA01 and GLA06 are the products used in this analysis. When fully calibrated, the global ICESat elevations are estimated to have an absolute accuracy of 2 to 7 cm and a precision of 2 to 3 cm at 40 Hz, tested over a variety of surfaces such as dry lakes and the Antarctic Dry Valleys Martin et al 2005;Magruder et al 2007). …”
Section: Icesat Datamentioning
confidence: 99%
“…Bhang et al [14] have demonstrated a difference between GLAS elevation and gauging stations between 2 and 35 cm for lakes in Otter Tail County, Minnesota (USA). Other studies have demonstrated that the accuracy of ICESat is greater than 10 cm, compared to gauge data [12,15,16]. However, the quality of ICESat data for rivers has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A 2 • slope, combined with the 1 arcsec positioning error results in an elevation error of 10 cm (Martin et al, 2005). Based on the new DEM presented here, the slopes at Halvfarryggen and Søråsen were calculated for 1 km × 1 km grid cells.…”
Section: Satellite Laser Altimetrymentioning
confidence: 99%